Performance comparison of some addition chain methods based on integer family - Kadir M.F.A.; Mohamed M.A.; Mohamad R.; Mamat M.; Muhammed A. (Springer Verlag, 2023)
Chains; Geometry; Public key cryptography; Addition chains; Competitive performance; Composition method; Computational resources; Elliptic curve cryptography; NP Complete; Performance comparison; Scalar multiplication; Heuristic methods